Assessment for Learning Berorientasi Higher Order Thinking Skills untuk Menstimulus Kecakapan Literasi Numerasi - Khoiriah, Khoiriah (Jurnal Didaktika Pendidikan Dasar, 2022)
This study aims to implement an assessment for learning oriented to higher order thinking skills to stimulate students' numeracy literacy skills. The research design used a pretest-posttest control group. The research sample involved two groups of students from twelve groups of eighth grade students at SMP Negeri 16 Bandar Lampung through random sampling. The data collection instruments were in the form of numeracy literacy skills test instruments and numeracy literacy skills observation instruments. Data were analyzed descriptively qualitatively and quantitatively with independent sample t test. The results of data analysis showed that the observation of students' numeracy literacy skills in the two experimental classes was categorized as "very high" with an average breakdown of 81,44% for the experimental class 1 and 81,93% for the experimental class 2, while the student's numeracy literacy proficiency test obtained a value of Sig (2-tailed)  < 0,05, namely Sig (2-tailed) = 0,000 which means that the hypothesis test is declared to reject H0 and accept H1. It can be concluded that the assessment for learning oriented to higher order thinking skills is effective in stimulating students' numeracy literacy skills.